HUBUNGAN TINGKAT PENGETAHUAN OSTEOPOROSIS DENGAN TINDAKAN PENCEGAHAN OSTEOPOROSIS PADA MAHASISWA FK UNPRI ANGKATAN 2019 - Adrian Khu; Aditya Syahputra; Meisya Melissa; Linda Chiuman (Universitas Prima Indonesia, 2022)
Osteoporosis doesn't only affect elderly people, but it can also appear in younger people. Therefore, we must have well prepare prevention at a young age to prevent osteoporosis at an older age. This study intends to see the correlation between the education level and with prevention measure of osteoporosis. It uses an analytical observational research design with a cross-sectional study approach. The respondent sample was 76 respondents which were calculated through the Slovin formula. This research was conducted by using a questionnaire. The result of the studies was analyzed using spearman correlation with Cronbach Alpha 0,05. Most of the resulting studies, contain 81,6% of people who have a good education level. 84,2% of respondents have a prevention measure mild. Spearman value (p=0,770), where p is larger than alpha (p>0,05). Therefore, it can be concluded there's no relation between the education level of osteoporosis and with prevention measure of osteoporosis. Furthermore, the correlation coefficient value (r = -0.034), which indicates the correlation strength is very low and has a negative correlation direction that can be concluded if the level of knowledge is good then the precautions will be bad and vice versa as well.